Aberrantly Expressed Small Noncoding RNAome in Keloid Skin Tissue - Yin, Chuang; Wang, Chuandong; Wang, Chen (Frontiers in Genetics, 2022)
Skin is a protective organ against injury and infection, thus easily damaged. Wound healing is therefore one of the most common physiological processes in the human body, but most complicated. Wound healing is a subtle balance, which once broken can lead to undesirable results like hypertrophic scar and keloid. Small non-coding RNA which composed by widely known housekeeping ncRNA like rRNAs and tRNAs and regulatory RNA such as microRNAs (miRNAs), small nucleolar RNA (snoRNAs), Piwi-interacting RNA (piRNAs). In the epigenetics study of keloids, researchers have focused on DNA methylations and ncRNA regulations, but other small noncoding RNA studies are still vacant. In this study we examined the five small noncoding RNAs (miRNA, piRNA, snoRNA, snRNA and rasiRNA) in keloid tissue using small RNA sequence and qPCR. The result showed that 3 piRNAs upregulated and 6 piRNAs downregulated in keloid tissues. As for snoRNA result showed 12 snoRNAs upregulated and 2 snoRNAs downregulated in keloid tissues. As for snRNA result showed 2 snRNAs downregulated in keloid tissues. As for miRNA result showed 18 miRNAs upregulated and 3 miRNAs downregulated in keloid tissues. As for rasiRNA result showed 1 rasiRNAs upregulated and 1 rasiRNAs downregulated in keloid tissues. Oure result revealed the differential expression small noncoding RNA in keloid tissues which may indicated for future keloid treatment.